EXPLORING THE SYNERGY BETWEEN HEALTHCARE ROLES AND REGIONAL DYNAMICS: A MULTIDISCIPLINARY PERSPECTIVE - Fatmah Sauqeer Nasser Almutery, Alanazi, Adel Farhan E. , Albanaqi, Farah Farhan Raja, Alenzi, Azizah Saud Daher, Almutery, Atmah Sauqeer Nasser, Alruwili, Bader Hamoud Azl, Alshammari, Sultan Mohammed Abdullah, Alanazi, Naif Matar; Khulaif Saud Albanaqi, Faisal khalid ayed aldhafeeri (Chelonian Research Foundation, 2022)
The healthcare industry is a complex system that involves the collaboration of various roles and disciplines to ensure the effective delivery of patient care. This study aims to explore the synergy between different healthcare roles and regional dynamics in Saudi Arabia from a multidisciplinary perspective. By examining the interplay between pharmacy technicians, nursing technicians, and other healthcare professionals, as well as the influence of regional factors, this research seeks to provide insights into the opportunities and challenges of fostering collaboration and optimizing healthcare outcomes. A mixed-methods approach, comprising surveys, interviews, and focus group discussions, was employed to gather data from a diverse sample of healthcare professionals across different regions in Saudi Arabia. The findings highlight the importance of effective communication, mutual respect, and shared goals in promoting synergy among healthcare roles. Additionally, the study reveals the impact of regional dynamics, such as cultural norms, resource availability, and policy frameworks, on the collaboration between healthcare professionals. The implications of this research for healthcare policy, practice, and education are discussed, emphasizing the need for a holistic and context-sensitive approach to enhancing the synergy between healthcare roles and regional dynamics in Saudi Arabia. Keywords: healthcare roles, regional dynamics, multidisciplinary collaboration, synergy, Saudi Arabia